Effect of profitability, audit committee, company size, activity, and board of directors on sustainability - Nawang Kalbuana; Kusiyah Kusiyah; Supriatiningsih Supriatiningsih; Roy Budiharjo; Triyani Budyastuti; Rusdiyanto Rusdiyanto (Cogent Business & Management, 2022)
This study aims to prove the consistency of Agency Theory as a solution to explain the role of the influence of Profitability Ratio, Activity, company size, audit committee and Board of Directors on Sustainability. This study uses a quantitative approach with population and research samples using companies listed in the Jakarta Islamic Index in 2017-2021. The data used in this study used panel data. One of the regression completion procedures with a high level of flexibility in research that connects theory, concepts, and data that can be done on research variables is used in this study's data analysis method: Regression Ordinary Least Square, Fixed Effects, Random Effects, Robust with Stata Software. The first finding explains that the Profitability Ratio has a negative effect on Sustainability, the second finding explains that the Activity Ratio does not have a positive effect on Sustainability, the third finding explains that the company size has a positive effect on Sustainability, the fourth finding explains that the audit committee has a negative effect on Sustainability, while the fifth finding explains that board of directors doesn't have a positive effect on Sustainability.
Keywords: G32; G34; G02; M1; Z1; 650; audit committee; Profitability; sustainability; board of directors; activity; company size